"No Fracking Way!" Documentary Film, Discursive Opportunity, and Local Opposition against Hydraulic Fracturing in the United States, 2010 to 2013. (October 2015) - Vasi, Ion Bogdan; Walker, Edward T.; Johnson, John S.; Tan, Hui Fen
Recent scholarship highlights the importance of public discourse for the mobilization and impact of social movements, but it neglects how cultural products may shift discourse and thereby influence mobilization and political outcomes. This study investigates how activism against hydraulic fracturing ("fracking") utilized cultural artifacts to influence public perceptions and effect change. A systematic analysis of Internet search data, social media postings, and newspaper articles allows us to identify how the documentary Gasland reshaped public discourse. We find that Gasland contributed not only to greater online searching about fracking, but also to increased social media chatter and heightened mass media coverage. Local screenings of Gasland contributed to anti-fracking mobilizations, which, in turn, affected the passage of local fracking moratoria in the Marcellus Shale states. These results have implications not only for understanding movement outcomes, but also for theory and research on media, the environment, and energy.